Exploring the Inhibitory Effects of Fucosylated Chondroitin Sulfate (FCS) Oligosaccharide Isolated from Stichopus horrens and the Derivatives on P-Selectin - Caiyi Li; Huifang Sun; Xi Gu; Wen Long; Guangyu Zhu; Xiaolu Wu; Yu Wang; Pengfei Li; Le Sha; Jiali Zhang; Wenwu Sun; Na Gao; et al. (Marine Drugs, 2025)
Unique fucosylated chondroitin sulfate (FCS) extracted from the sea cucumber Stichopus horrens was subjected to deacetylation and deaminative depolymerization to generate oligosaccharide fragments containing anTal-diol, which were further purified to obtain the trisaccharide ShFCS-3. Subsequently, the coupling of ShFCS-3 and 4-azidoaniline was achieved by reductive amination. After purification, the main product ShFCS-A1 and by-product ShFCS-A2 were obtained, which were identified as (N-(L-Fuc2S4S-α1,3-D-GlcA-β1,3-D-anTalA4S6S-1-)-4-azidoaniline) and (4S)-[2-(3-L-Fuc2S4S-α1)-D-GlcA-β1]-2,4,5-trihydroxy-5-sulfated-pent-2-enoic-acid) by 1D/2D NMR spectroscopy, respectively. ELISA experiments revealed that ShFCS-A1 exhibited P-selectin inhibition rates of 19.73% ± 9.60% at 1 μM, 96.28% ± 2.37% at 10 μM, and near-complete inhibition (99.92% ± 0.84%) at 100 μM. ShFCS-A2 demonstrated inhibition rates of 8.29% ± 3.00% at 1 μM, 74.02% ± 8.80% at 10 μM, and maximal inhibition approaching 100% at 100 μM. Cellular-level experiments revealed that ShFCS-A1 and ShFCS-A2 inhibited P-selectin binding to HL-60 cells by 92.72% ± 0.85% and 96.97% ± 1.16% at 100 μM, respectively. Molecular docking analysis indicated binding energies of −5.954 kcal/mol for ShFCS-A1 and −6.140 kcal/mol for ShFCS-A2 with P-selectin, confirming their potent inhibitory effects. These findings highlight the therapeutic potential of FCS oligosaccharides as pharmacophores and provide an important foundation for developing novel small-molecule P-selectin inhibitors.